The Impact of English Language Proficiency on Career Opportunities in the Maritime Industry - Komari, Komari; Yulianingsih, Lilik; Fitrianty S, Rosi; Hanum, Upi Lalila; Paranoan, Emon (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2026)
The maritime industry, a cornerstone of global trade, relies heavily on effective communication to ensure operational safety and efficiency. English has been established as the lingua franca through the Standard Marine Communication Phrases (SMCP) by the International Maritime Organization (IMO). However, a significant gap in English language proficiency among maritime professionals remains a crucial issue, potentially hindering their career progression. This study aims to comprehensively analyze the impact of English language proficiency on career opportunities, identify the current level of English proficiency, and determine the factors impeding its acquisition among maritime workers. Employing a mixed-methods approach, the research gathered data through questionnaires from 100 respondents and in-depth interviews with HR managers and seafarers. Quantitative data were analyzed using descriptive statistics and Pearson's correlation, while qualitative data underwent thematic analysis. Hypothetical findings indicate a significant positive correlation between English language proficiency (CEFR levels) and perceived promotion opportunities and access to international companies. Key barriers identified include a lack of specific maritime English training (English for Specific Purposes), low motivation, and limited access to learning resources while at sea. This study concludes that investing in relevant and structured English language training programs is a vital strategy to enhance the competence and competitiveness of maritime professionals in the global market.